Chemical speciation of CO2 absorption in aqueous monoethanolamine investigated by in situ Raman spectroscopy - Wong, M.K. (Elsevier Ltd, 2015)
A quantitative analysis method of chemical species in liquid phase during CO2 absorption into monoethanolamine was developed for Raman spectroscopy. Band envelopes in the spectral region between 300 and 3100cm-1 were resolved with Gaussian Lorentzian function. Spectroscopic characterization of MEA, protonated MEA, carbamate, bicarbonate, carbonate and molecular CO2 in aqueous was performed. Calibration curves were constructed with area ratio plotted against species concentration. Concentration of individual chemical species in liquid phase can be systematically determined using the correlations introduced. Experiments of CO2 solubility in aqueous MEA were carried out for pressure ranges from 1 to 60bar and three temperatures (303.15, 313.15 and 323.15) K with in situ Raman measurement. Absorption capacity was determined with conventional gas pressure drop method and newly developed Raman spectroscopic analysis method based on total carbon containing species in liquid phase. Results depict good accuracy and reproducibility of Raman measurement method. Chemical speciation during CO2 absorption into aqueous solution of 30 MEA at pressure up to 60bar was evaluated. The findings from present work will improve the understanding of phase equilibrium behavior associated with absorption reactions and can be employed for monitoring, analysis and optimization of CO2 capture process. Â© 2015 Elsevier Ltd.